UWE-3, in-orbit performance and lessons learned of a modular and flexible satellite bus for future pico-satellite formations. (December 2015) - Busch, S.; Bangert, P.; Dombrovski, S.; Schilling, K.
Abstract: Formations of small satellites offer promising perspectives due to improved temporal and spatial coverage and resolution at reasonable costs. The UWE-program addresses in-orbit demonstrations of key technologies to enable formations of cooperating distributed spacecraft at pico-satellite level. In this context, the CubeSat UWE-3 addresses experiments for evaluation of real-time attitude determination and control. UWE-3 introduces also a modular and flexible pico-satellite bus as a robust and extensible base for future missions. Technical objective was a very low power consumption of the COTS-based system, nevertheless providing a robust performance of this miniature satellite by advanced microprocessor redundancy and fault detection, identification and recovery software. This contribution addresses the UWE-3 design and mission results with emphasis on the operational experiences of the attitude determination and control system. Highlights: Design aspects and first year in-orbit experience of the modular pico-satellite UWE-3. Performance demonstration based on in-orbit data of individual subsystems. Characterization of residual magnetic dipole moment affecting attitude control. Results from efficient magnetic control for spin-up and detumbling experiments. Location and frequency analysis of interference sources in the amateur radio band.